A review on the effect of biofilm thickness in moving bed bioreactor for the nitrogen compounds removal - Danial Nayeri; Samira Khamutian; Mohammad Javad Shokoohizadeh (Desalination and Water Treatment)
Moving bed biofilm reactor (MBBR) has picked up consideration since of its compactness, simplicity, stability that reinforces circularity in the wastewater treatment industry in line with the principles of the circular economy. In biofilm reactors, especially MBBR, biofilm thickness plays a significant role in creating aerobic presence, anoxic, and anaerobic zones, which are responsible for simultaneous nitrification-denitrification (SND) processes and subsequently reactor efficiency. Therefore, this review aims to investigate the effect of different factors (biocarrier type, filling fraction (%), dissolved oxygen (DO), hydraulic retention time (HRT), and temperature) upon biofilm thickness in MBBRs used for nitrogen compounds removal, identifying the dominant microorganisms in the biofilm, and some future challenges and prospects of MBBRs have discussed. The results showed that the optimal biofilm thickness for nitrification alone is around 100–200 μm, while for SND, it should be at least 500 μm, with a reactor filling fraction between 30 % and 50 %. Kaldness media demonstrated significant higher nitrogenous compunds removal, lower solids production, higher biofilm thickness as well as greater stability compared to the others. The study also found that MBBRs can perform nitrification and denitrification processes at different temperature ranges, even at 1 and 2 °C. The dominant microbial community in the biofilm consist bacteroides, protobacteria, primarily of ammonium oxidizing bacteria (AOB), and nitrate oxidizing bacteria (NOB), all of which play a crucial role in the wastewater treatment process. The results of this review give useful knowledge for the optimization of MBBRs and accomplish the future goal of nitrogen compounds removal from wastewater.